The best worst thing - Lane, Kathleen, 1967- (Little, Brown and Company, 2018)
Ever since starting middle school, Maggie has been worried. She sees injustice and danger everywhere, even in her own neighborhood, even in the changes that seem to be happening with her best friend. Well, it seems like it is up to Maggie to make everything right, but when she tries to come up with a plan to control everything in her life, she learns that sometimes it is best to let things go by themselves.